Survey of Students' Basic Handball Technical Abilities in Extracurricular Activities at State Senior High School 7 Prabumulih - Prastyo, Dwi Aji; Wardiah, Dessy; Lanos, Muhsana El Cintami (STKIP PGRI Trenggalek, 2026)
Basic technical skills are the main components that determine the success of coaching and handball performance. This study aims to analyze the level of basic technical ability of handball games of students who participate in extracurricular activities at SMA Negeri 7 Prabumulih. The research uses a quantitative approach with a descriptive survey design. The sample amounted to 15 students who were selected using a simple random sampling technique from a population of 61 students. Data was collected through basic technical ability tests that included passing, dribbling, and shooting, and supported by observation and documentation. Data analysis used descriptive statistics in the form of average scores, percentages, and distribution of ability categories. The results of the study show that the basic engineering skills of students are in the category of quite good to very good. Passing ability obtained an average score of 53.93 (quite good), dribbling obtained an average time of 13.60 seconds (good), while shooting obtained an average score of 8.73 (very good). The observation results show that the training program has been carried out very well, although passing ability still needs to be improved to be more even. These findings provide an empirical basis for the evaluation and preparation of more effective handball training programs according to the needs of students in extracurricular activities